Desain dan Pengembangan Materi Pembelajaran Keterampilan Reseptif Bahasa Arab: Mahārah Istimā’ dan Qirā’ah - Muslimin Resi; Wilda Widya Armadani; Andi Nur Pratiwi; Hamzah Hamzah; Kaharuddin Kaharuddin (Diwan Media Pustaka, 2025)
This study discusses the design and development of Arabic receptive skills learning materials, which include mahārah istimā' (listening skills) and mahārah qirā’ah (reading skills). This topic was chosen because receptive skills play an important role as the foundation of Arabic language acquisition; however, in practice, the learning process of listening and reading skills still faces various problems, such as limited vocabulary mastery, a lack of varied learning media, and learning materials that are not yet suited to students' needs. This study aims to describe the concept of Arabic receptive skills, explain the principles of effective learning material design, and examine the steps for developing listening and reading learning materials. This research employed a qualitative approach with a library research method. The data were obtained from various sources, including books, journals, research articles, and academic documents on Arabic language learning. Data collection was conducted through documentation techniques, while data analysis used the Miles and Huberman interactive model, which consists of data reduction, data presentation, and conclusion drawing. The results of the study indicate that effective receptive skills learning materials should be designed based on gradual, communicative, relevant, and contextual principles. In addition, the use of audio media, texts, and digital technology has proven to improve students' motivation and comprehension in Arabic language learning. The development of interactive learning activities also encourages students to become more active in understanding conversations and Arabic texts. Therefore, the design and development of innovative learning materials that are suited to students' needs are essential for improving the quality of mahārah istimā' and mahārah qirā’ah learning in modern Arabic language education.